Interactions of chlorine with tropical aquatic fulvic acids and formation of intermediates observed by fluorescence spectroscopy - Carvalho, Eduarda R.; Martin-Neto, Ladislau; Milori, Débora M. B. P.; Rocha, Julio C. [UNESP]; Rosa, André H. [UNESP] (FapUNIFESP (SciELO), 2004)
The interactions of tropical aquatic fulvic acids (AFA) with chlorine and formation of trihalomethanes were characterized by fluorescence spectroscopy. The aquatic humic substances (AHS) were isolated from a dark-brown stream (located in a environmental protection area near Cubatão city in São Paulo State, Brazil) by means of the collector XAD 8 according the procedure recommended by the International Humic Substances Society. The photoluminescence measurements were made by using a Perkin Elmer spectrometer; AHS, aquatic humic acids (AHA) and AFA samples were assayed. The interactions of AFA and chlorine were characterized by using different reaction times (1, 24, 48, 72 and 168 h) and chlorine concentrations (2.5, 5.0, 10.0 and 20.0 mg L-1). The relative fluorescence intensity for AFA was significantly decreased with the increasing of chlorine concentration and reaction time. The reduction of fluorescence intensity in the region of longer wavelength was interpreted as an indicative of interaction between condensed aromatic groups of AFA and chlorine.
Keywords: Aquatic fulvic acids; Aquatic humic substances; Natural waters; Photoluminescence; Trihalomethanes; adsorbent; aromatic compound; chlorine; fulvic acid; trihalomethane; assay; Brazil; chemical analysis; chemical interaction; color; concentration (parameters); environmental protection; fluorescence; fluorescence spectroscopy; humic substance; isolation procedure; measurement; observation; photoluminescence; polymerization; reaction time; spectrometer; synthesis